The Effect of Loose Parts Media on Early Childhood Visual-Spatial Intelligence - Jhoni Warmansyah; Sari Ramadona; Eliza Febriyani; Aisyah Safna; Mila Karlaini (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to determine the effect of loose parts media on visual-spatial intelligence in early childhood. This study used an experimental method with a pre-experimental type one group pretest-posttest design. This Study used simple random sampling technique. The data collection technique used is a visual-spatial intelligence observation sheet. Data analysis technique using a t-test. The results showed that there was an effect of loose parts media on visual-spatial intelligence from the pretest, the treatment I to IV, and the posttest series. This is clear from the previous pretest average result which was 13.71, now the average has increased to 36.57 after being given treatment as using loose part media and the t-count is greater than the t-table which is 47.60> 2.160. This means that loose parts of media can affect the visualspatial intelligence of early childhood. These loose parts are an alternative media that teachers can use to stimulate children’s visual-spatial intelligence.